1985
DOI: 10.1002/jnr.490140210
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the blood‐brain barrier in hyperammonemic coma and the pharmacologic effects of dexamethasone and difluoromethyl ornithine

Abstract: Both hyperammonemia and blood-brain barrier (BBB) breakdown have been implicated in the evolution of hepatic encephalopathy. To define a possible relationship, Swiss Albino mice were subjected to sublethal encephalopathic doses of ammonium acetate; the integrity of the BBB was determined grossly with Evans blue and quantitatively with [14C]-alpha-aminoisobutyrate (AIB). Some animals were injected with a dose of ammonium acetate sufficient to maintain coma for 1 hr (AC group). One group, termed stuporous (AS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

1990
1990
1993
1993

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
4
14
0
Order By: Relevance
“…All the animals in this group developed sublethal coma, in agreement with the original description of the model (Sears et al, 1985). In the "subchronic" group, both blood and brain ammonia were about 60% higher than in (9) 0.24 ± 0.04 (8) "Acute" 1500 t 50 (5) 1.35 ± 0.19 (9) "Subchronic" 160 ± 6 (5) 0.37 ± 0.03 (8) "Chronic" 219 ± 19 (6) 0.38 ± 0.02 (8) Results are mean ± SD, with number of experiments in parentheses.…”
Section: Pathophysiological Characteristics Of the Three Variants Of supporting
confidence: 70%
See 2 more Smart Citations
“…All the animals in this group developed sublethal coma, in agreement with the original description of the model (Sears et al, 1985). In the "subchronic" group, both blood and brain ammonia were about 60% higher than in (9) 0.24 ± 0.04 (8) "Acute" 1500 t 50 (5) 1.35 ± 0.19 (9) "Subchronic" 160 ± 6 (5) 0.37 ± 0.03 (8) "Chronic" 219 ± 19 (6) 0.38 ± 0.02 (8) Results are mean ± SD, with number of experiments in parentheses.…”
Section: Pathophysiological Characteristics Of the Three Variants Of supporting
confidence: 70%
“…control rats (Table 1). In its behavioral pattern, the group resembled the "stuporous" group described by Sears et al (1985); the animals showed a severe impairment, but not a complete block of the righting response. In "chronic" hyperammonemia, blood ammonia was two times higher than control, whereas brain ammonia showed a 60% increase.…”
Section: Pathophysiological Characteristics Of the Three Variants Of mentioning
confidence: 80%
See 1 more Smart Citation
“…Several lines of evidence have been presented indicating that activation of polyamine synthesis may play a pivotal role in disturbances of the blood-brain barrier under different experimental conditions including cold lesion to the brain, hyperosmolal opening of the blood-brain barrier and disruption of the blood-brain barrier in hyperammonemic coma (Koenig et al, 1983a(Koenig et al, , 1989aSears et al, 1985;Trout et al, 1986). The first results indicating that blood-brain barrier breakdown may be triggered by an activation of polyamine synthesis were published by Koenig et al (1983a) using a cryogenic lesion of the rat cerebral cortex as model.…”
Section: Blood-brain Barrier Disturbancesmentioning
confidence: 99%
“…In a third series of experiments, ammonium acetate was used to study the effect of hyperammonemia as a model of hepathic encephalopathy on the integrity of the blood-brain barrier (Sears et al, 1985). When measured with Evans blue or [ 14 C]aminoisobutyrate, hyperammonemia produced marked disturbances of the blood-brain barrier, which were completely suppressed in animals pretreated with DFMO.…”
Section: Blood-brain Barrier Disturbancesmentioning
confidence: 99%